Combining EBR CFRP sheet with prestressed NSM steel strands to enhance the structural behavior of prestressed concrete beams - Obaydullah, M.; Jumaat, Mohd Zamin; Alengaram, U. Johnson; Kabir, Md. Humayun; Rashid, Muhammad Harunur (Journal of Civil Engineering and Management, 2021)
In this study, a combined strengthening technique is used to improve the flexural performance of prestressed concrete beams using CFRP sheets as EBR and prestressed steel strands as NSM. Seven prestressed beams were tested under four-point loading with one control specimen, one EBR CFRP sheet strengthened specimen, one NSM steel strand without prestress strengthened specimen and four specimens strengthened with a combination of EBR CFRP sheet and NSM steel strands prestressed from 0% to 70% of their tensile strength. The flexural responses and failure modes of the specimens were investigated and the variations due to the level of prestressing force in the PNSM steel strands were also assessed. A finite element model (FEM) was developed using ABAQUS to verify the flexural responses of the strengthened specimens. The test results revealed that the combined strengthening technique remarkably enhanced the flexural performance of the specimens. The serviceability, first crack, yield, and ultimate load capacities improved up to 44%, 49%, 55% and 70%, respectively when compared with the control specimen. The combined technique also ensured the flexural failure of the specimens with significant enhancement in stiffness and energy absorption. The results of the FEM model exhibited excellent agreement with the experimental results.